Entropy generation of two-layer magnetohydrodynamic electroosmotic flow through microparallel channels. (15th November 2017) - Xie, Zhi-Yong; Jian, Yong-Jun
Abstract: The entropy generation analysis of two-layer magnetohydrodynamic electroosmotic flow through a microparallel channel is performed in this study. The two immiscible fluid flows are both driven by a combination of electroosmotic force, pressure gradient and electromagnetic force. Under the framework of Debye-Hückel linearization approximation as well as the assumption of thermally fully developed and the condition of constant wall heat flux, the distributions of velocity and temperature are analytically derived and they are utilized to compute the entropy generation rate. The effects of fluid physical parameter ratios on the distributions of two-layer fluid velocity and temperature are firstly discussed. Then the local and total entropy generation rates are investigated for different magnetic field parameter ( Ha ) and the viscous dissipation parameter ( Br ) under the appropriate fluid physical parameter ratios. The results show that the entropy generation rate strongly depends on the velocity and temperature fields and the local entropy generation reveals a decreasing trend form the microchannel wall towards the fluid interface for both bottom and upper layer fluid. The present endeavor can be utilized to design the efficient thermal micro-equipment. Highlights: Magnetohydrodynamic electroosmotic flow is investigated. The analytical solutions of velocity and temperature are derived. A comparison of analytical and numerical temperature distributions is performed. The dependence of the entropy generation rate on related parameters is discussed.